(untitled) (Journal of Philosophy Culture and Political Science, 2023)
This article analyzes the key functions of the Horde’s Muslim clergy since the founding of the Bokey Khanate, and the peculiarities of Zhangir Khan’s system of Muslim management. In the early years of the Horde’s establishment, it became clear that religious affairs, including the Muslim administration, were carried out under the direct administration of the tsar’s administration. Officially, during the reign of Zhangir Khan, the highest instance of the Muslim rule was Ahun, and then the Mullahs. But Ahun himself was appointed by the khan. The khan himself also ordered the appointment of the Mullahs, and ordered the appointment. It was evident that in the Horde’s territory there was a shortage of Muslim priests in the early days and an increasing number of priests during the Zhangir period. In addition, another document that highlights the topic, items contained in the orders of Zhangir Khan on the appointment of a mullah or akhun, were differentiated as the primary source reflecting the peculiarities of Muslim rule in the Bokey Horde. Кілт сөздер: Бөкей Орда, Ислам, діни басқару, Жәңгір хан, патшалық Ресей